2003
DOI: 10.2320/matertrans.44.1448
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the β-AlFeSi to α-Al(FeMn)Si Transformation in Al-Mg-Si Alloys

Abstract: During the homogenisation process of Al-Mg-Si extrusion alloys, plate-like -Al 5 FeSi particles transform to multiple roundedAl 12 (FeMn) 3 Si particles. The rate of this to transformation determines the time which is required to homogenise the aluminium sufficiently for extrusion. In this paper, a finite element approach is presented which model the development of fraction transformed with time, in the beginning of the transformation, as a function of homogenisation temperature, as-cast microstructure and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 26 publications
3
32
0
Order By: Relevance
“…Kuijpers et al [11] suggested this transformation is solute diffusion controlled, initiated by the a c -AlFeSi nucleation on the basal face of b-AlFeSi platelets; the b-AlFeSi then dissolves and a c -AlFeSi grows by consuming released Fe, Mn and Si. They also observed an increase in Mn content in a c -AlFeSi particles after homogenization due to longer diffusion times.…”
Section: B Evolution Of Fe-imcs During Homogenizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuijpers et al [11] suggested this transformation is solute diffusion controlled, initiated by the a c -AlFeSi nucleation on the basal face of b-AlFeSi platelets; the b-AlFeSi then dissolves and a c -AlFeSi grows by consuming released Fe, Mn and Si. They also observed an increase in Mn content in a c -AlFeSi particles after homogenization due to longer diffusion times.…”
Section: B Evolution Of Fe-imcs During Homogenizationmentioning
confidence: 99%
“…[6] Therefore, a post-cast homogenization heat treatment is used commercially to encourage transformation of b to a to allow: (a) more reliable downstream deformation, typically by extrusion, (b) improved mechanical properties, especially toughness and elongation to failure, and (c) improved surface finish. [5,[10][11][12][13][14][15][16] Despite the apparent maturity of AA6xxx alloys, there is a significant on-going effort to optimize homogenization conditions in terms of properties, while also minimizing the homogenization time. Among the factors that govern the homogenization response, the initial cast microstructure and the alloy chemical composition play key roles.…”
Section: Introductionmentioning
confidence: 99%
“…Either because of an intrinsic brittleness or because of a lack of coherence with the matrix, these particles will result in a damage initiation owing to the nucleation of small internal voids, which develop into cracks when exposed to stresses [38,39]. The plate-like particles can lead to a crack initiation and induce surface defects in the deformed material [42]. In these sheets, it is possible that the deformation of Fe-Cr-Mn-Si particles results in some micro-defects in sheets with increasing the number of passes, as shown in Fig.…”
Section: Strength Of As-rolled and Aged Sheetsmentioning
confidence: 99%
“…implicit) direct numerical approach, e.g. the finite difference method (FDM), 9,10) the finite element method (FEM), 11) or the boundary element method (BEM) 12) is necessary for the TSMP. For this approach, a significantly large calculation cost is inevitable because a rather small time increment compared with the required casting time is necessary; the time increment is limited by the Courant-Friedrich-Levy (CFL) condition, which governs the calculation stability and accuracy, even in an implicit method because of the special limitation for solidification analysis.…”
Section: Direct Numerical Approachmentioning
confidence: 99%